The Nature of Fiscal Policy in Islam as an Effort to Realize The Concept of Prosperity - Nasrudin Nasrudin (JES (Jurnal Ekonomi Syariah), 2023)
This study aims to find out and explain about the nature of fiscal policy in Islam as an effort to create a society based on a balanced wealth distribution. This research is descriptive analysis using qualitative data as the type of research and literature study as one of the data collection techniques. This research concludes that: First, in Islam there are limits on fiscal policy as a step to change the tax or expenditure system with the aim of overcoming the economic problems faced by the government; Second, Islamic fiscal policy became part of the religious (diyanatan) and state (qadaan) provisions; Third, fiscal policy instruments in Islam include state revenues and expenditures, which in turn are managed to realize the concept of prosperity.